The Effect Of Giving Sweet Potatoes Leaves (Ipomoea Batatas L.) On Breast Milk Production - Cecen Suci Hakameri Hakameri; Nur Israyati (Institute of Computer Science (IOCS), 2022)
Exclusive breastfeeding contributes to reducing mortality due to infection in infants less than 3 months old, sick children, preventing LBW, stunting, reducing the risk of obesity and chronic diseases. Physiologically a mother is able to produce sufficient breast milk. But sometimes in breastfeeding there are often problems, one of which is the mother's milk production that is not smooth and comes out a little. Based on research, one of the efforts to help increase breast milk production is to consume sweet potato leaves (Ipomoea Batatas L. ) contains phytosterols. Phytosterols form laktogogum which can increase milk production. The purpose of the study was to determine the effect of sweet potato leaves (Ipomoea Batatas L.) on breast milk production in post partum mothers. This type of research is Pre experimental with one group pretest posttest designs. The time of the research was carried out in January – April 2022. The location of the research was in Karya Indah Village, Tapung District, Kampar Regency. The sample in this study were 20 respondents with total sampling technique. The research instrument used an observation sheet for breast milk production. Univariate and bivariate data analysis. Univariate results showed that the average milk production before being given sweet potato leaves was less with a percentage of 75% and after being given sweet potato leaves the average milk production increased to enough with a percentage of 90%. Bivariate results using the Wilcoxon Rank Test showed that the average milk production before being given sweet potato leaves was 4.13 mL and there was an increase in breast milk production after being given sweet potato leaves, the mean value was 35.9 mL. with a mean difference of 31.7. The results of the Wilcoxon Rank Test obtained a p value of 0.000 (p <0.05). So it can be concluded that there is an effect of sweet potato leaves on breast milk production in post partum mothers in Karya Indah Village, Tapung District, Kampar Regency. It is hoped that in the future the consumption of sweet potato leaves will be introduced in the community as an alternative food to increase breast milk production.